Professional development and career planning for nurses working in care homes for older people: A scoping review. (28th November 2022) - Fitzpatrick, Joanne M.; Bianchi, Leda A.; Hayes, Nicky; Da Silva, Tiago; Harris, Ruth
Abstract: Background: A skilled, knowledgeable, and compassionate nurse workforce is pivotal to caring well for older people living in care homes. This requires the provision of continuing professional development and career planning for nurses, which are key also for nurse recruitment and retention. Continuing professional development and career planning strategies and interventions should be evidence‐driven. Objective: To identify the extent, range and nature of contemporary evidence regarding professional development and career planning for nurses caring for older people living in care homes. Methods: The methodological framework used was the Joanna Briggs Institute guidance for scoping reviews. The PRISMA extension for scoping reviews was used as the reporting framework. Four databases were searched from January 2010 to July 2021. Results were screened independently by two reviewers using eligibility criteria. Full texts and the reference lists of eligible articles were reviewed. Data were extracted for key elements from the 25 articles included. Results: Of the 25 articles, the majority were authored in the United States ( n  = 10) and UK ( n  = 8) with the remaining from Australia ( n  = 3), Canada ( n  = 3) and the Netherlands ( n  = 1). Four articles reported on professional development programmes. Three literature reviews addressed challenges for nurse participation in professional development, experiences of care home nurses as clinical leaders and managers, and leadership. Two expert commentaries reported on the challenges related to professional development and career planning for care home nurses. Sixteen empirical studies investigated a range of topics including: competencies, roles, intention to stay and leave, continuing professional development, and leadership. Key emergent factors that support professional development and career planning were as follows: access to structured learning opportunities addressing knowledge and skills specific to nursing frail older adults, a supportive working environment including adequate staffing, study time and flexible working, and integration of leadership development. Conclusions and implications for practice: This scoping review has highlighted factors that support and challenge professional development and career planning for nurses working in the care home sector. There remain important gaps in the opportunities for professional development and career planning for care home nurses that warrant attention.